20.2k views
0 votes
Select the correct answer. Which statement is true about this equation? -(2x + 4) + x = 3x − 4x − 4

User Dayamoy
by
5.6k points

2 Answers

4 votes

Answer:

Infinite number of solutions

Explanation:

-(2x + 4) + x = 3x − 4x − 4

-2x - 4 + x = -x - 4

-x - 4 = -x - 4

-4 = -4

This equation remains true for all x,

Hence infinitely many solutions

User WisdomPill
by
6.8k points
6 votes

Answer:

no solutions

Explanation:

-(2x + 4) + x = 3x − 4x − 4

Distribute

-2x - 4 + x = 3x − 4x − 4

Combine like terms

-x +4 = -x -4

Add x to each side

-x+x+4 = -x+x-4

4 = -4

This is never true so there are no solutions

User Nitish Dhar
by
6.5k points